2020
DOI: 10.3390/molecules25030436
|View full text |Cite
|
Sign up to set email alerts
|

Adduct under Field—A Qualitative Approach to Account for Solvent Effect on Hydrogen Bonding

Abstract: The location of a mobile proton in acid-base complexes in aprotic solvents can be predicted using a simplified Adduct under Field (AuF) approach, where solute–solvent effects on the geometry of hydrogen bond are simulated using a fictitious external electric field. The parameters of the field have been estimated using experimental data on acid-base complexes in CDF3/CDClF2. With some limitations, they can be applied to the chemically similar CHCl3 and CH2Cl2. The obtained data indicate that the solute–solvent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…This fact supports the possibility to observe the tautomeric equilibrium with double proton transfer ( Figure 5 B,C) in an experiment. Taking into account that the PCM approximation strongly underestimates the effect of polar media on hydrogen-bonded systems [ 66 , 67 , 68 , 69 ], one can expect a fast, concerted proton transfer in phthalic acid dimers in polar solvents. Previously, a double proton transfer in carboxylic acid dimers was experimentally detected in low-temperature NMR spectra (110 K, CDF 3 /CDF 2 Cl mixture as solvent) as a triplet splitting of the bridging proton signal for 13 C-labelled acetic acid due to 2 J (C,H) spin-spin coupling [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact supports the possibility to observe the tautomeric equilibrium with double proton transfer ( Figure 5 B,C) in an experiment. Taking into account that the PCM approximation strongly underestimates the effect of polar media on hydrogen-bonded systems [ 66 , 67 , 68 , 69 ], one can expect a fast, concerted proton transfer in phthalic acid dimers in polar solvents. Previously, a double proton transfer in carboxylic acid dimers was experimentally detected in low-temperature NMR spectra (110 K, CDF 3 /CDF 2 Cl mixture as solvent) as a triplet splitting of the bridging proton signal for 13 C-labelled acetic acid due to 2 J (C,H) spin-spin coupling [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result depends on the position of the bonding proton with respect to the H-bond center. However, the reduction of solvent polarity causes the opposite effect [ 66 , 67 , 68 ]. We concluded that the 1 H chemical shift of the proton in the intermolecular H-bonds in scenarios a , b , and c should have been between 19 and 17 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Lesnichin et al [ 249 ] investigated the behavior of 2,2′-bipyridyl in confinement. They found that the molecule can only form one of the two possible hydrogen bonds to the surface and that the surface coverage grows strongly from one molecule per nm 2 at room temperature to 1.6 molecules per nm 2 at 130 K. Very recently, Shenderovich and Denisov studied the hydrogen bonding of pyridine in detail [ 252 ].…”
Section: Simple Liquids In Confinementmentioning
confidence: 99%
“…This concept is claimed to allow the universal application of the SMD model for any solvents and any (both charged and uncharged) solutes, yet it was shown that the original SMD parametrization can be not optimal [47][48][49]. Among the new developments of environment treatment, one can mention the Adduct-under-Field (AuF) approach proposed by Shenderovich and Denisov [50][51][52] where environment effects are simulated by the presence of the fictitious external electric field.…”
Section: Introductionmentioning
confidence: 99%